Self-Efficacy in English Listening - Sari Setiawati; Ikhsanudin Ikhsanudin; Dwi Riyanti (FKIP - Universitas Tanjungpura, 2023)
Every English student has to have some level of self-efficacy in listening. The purpose of this study was to look into a seventh-grade student's self-efficacy in listening to English in a junior high school in Kubu Raya. In this case study the researcher implemented participant observation, document gathering, and semi-structured interviews. The research subject is a seventh-grade student at a Madrasah Tsanawiyah in Kubu Raya. Descriptive analysis, data gathering, data reduction, data display, conclusion, or verification were all applied in data analysis. The data showed that a seventh-grade student's self-efficacy in listening to English is high. It was demonstrated by the subject's strengths, which include self-efficacy, dependability, and constancy. It can be said that students with high self-efficacy will behave favorably toward their English listening abilities; these students typically put a lot of effort into challenging tasks, are skilled at using a variety of strategies to overcome challenges, and have strong persistence in their English listening. To overcome the barrier of learning English by hearing, an English learner must have great self-efficacy.